Novozym 435 displays very different selectivity compared to lipase from Candida antarctica B adsorbed on other hydrophobic supports - Cabrera, Z.; Fernandez-Lorente, G.; Fernandez-Lafuente, G.; Palomo, J.M.; Guisan, J.M.
This paper shows that the properties of lipase B fromCandida antarctica (CAL-B)may be easily modulated using different hydrophobic supports to immobilize it (octyl and butyl-agarose, octadecyl-Sepabeads or Lewatit). CAL-B could be fully desorbed from the supports by just incubating the biocatalyst with Triton X-100, although the concentration of detergent necessary was to fully desorb the enzyme varied with the support employed (from 1
Keywords: LEWATIT; INTERFACIAL ACTIVATION OF LIPASES; ENANTIOSELECTIVITY; HYDROPHOBIC SUPPORTS; MODULATION OF ENZYME PROPERTIES; MANDELIC ACID; 3-PHENYLGLUTARIC ACID DIMETHYL DIESTER